Stochastic parameterizing manifolds and non-markovian reduced equations : stochastic manifolds for nonlinear SPDEs II /: stochastic manifolds for nonlinear SPDEs II. (2015) - Chekroun, Mickaël D; Liu, Honghu; Wang, Shouhong
No abstract available